A Biopsychosocial Model of Chronic Pain for Older Adults. Issue 9 (17th December 2019) - Miaskowski, Christine; Blyth, Fiona; Nicosia, Francesca; Haan, Mary; Keefe, Frances; Smith, Alexander; Ritchie, Christine
Abstract: Population: Comprehensive evaluation of chronic pain in older adults is multifaceted. Objective and Methods: Research on chronic pain in older adults needs to be guided by sound conceptual models. The purpose of this paper is to describe an adaptation of the Biopsychosocial Model (BPS) of Chronic Pain for older adults. The extant literature was reviewed, and selected research findings that provide the empiric foundation for this adaptation of the BPS model of chronic pain are summarized. The paper concludes with a discussion of specific recommendations for how this adapted model can be used to guide future research. Conclusions: This adaptation of the BPS model of chronic pain for older adults provides a comprehensive framework to guide future research in this vulnerable population.